Impacts of COVID-19 Pandemic on International Trade in Goods of OECD Countries - Ha, Le Thi (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2021)
The aim of this research is to analyze influences of the COVID-19 pandemic on international trade in goods of OECD countries. It is still too early to make an assessment of the impact of the virus based on full statistical evidence. Hence, we investigate trade among 37 OECD countries in 2019 and 2020 (trade data from OECD) to compare changes in global trade before COVID-19 (in 2019) and in the time of COVID-19 (in 2020). The disease burden of COVID-19 is measured in terms of the number of cases and deaths. We get COVID-19 data from the World Health Organization (WHO) monthly, trade data from OECD quarterly for a trade model that is based on the standard trade gravity variable from the  CEPII gravity database [1]. Our findings can be summarized as follows: First, the COVID-19 pandemic has negative effects on the international trade of OECD countries, particularly exporting countries, because the development of the COVID-19 pandemic prevents trading activities worldwide. Meanwhile, the COVID-19 pandemic has positive affects on importing countries because of demand for medical goods or essential foods. However, the level of the COVID-19 effect on exporting countries is much bigger than for importing countries; COVID-19 is truly a disaster for our world. Second, trade policy measures of the response to the COVID-19 pandemic have led to negative effects in the short-term, but in the long-term these measures create positive impacts on international trade and economics as well.